Uneven spatial development at the end of the world: Production of space and urban inequalities in Ushuaia and Río Grande - Fank, Lucía (2024)
This thesis addresses the process of uneven spatial development (USD), resulting from territorial expansion of capitalist economic activities (Smith, 2020). As long as new territories are incorporated into the accumulation process, simultaneous dynamics of equalization (of productive forms) and differentiation (of spatial forms) are generated in them. As a result, specific patterns of spatial inequality emerge, acquiring particular characteristics in the different scales and geographies (Smith, 2012; Brenner, 2009). Considering a Latin American approach, urban inequalities remain particular interest, given the fact cities concentrate most of the resources and the population. The State is crucial in defining the precise patterns that USD acquires through its economic and urban-territorial policies. This research frames the study problem in the context of national territory of Tierra del Fuego (TDF), Antarctica, and the South Atlantic Islands, constituted as a province of Argentine Republic in 1991. Due to geopolitical issues related to its strategic location in the South Atlantic Ocean, the Argentine government promoted specific policies in order to encourage its population. To accomplish this purpose, this territory was defined a Special Economic Zone (SEZ) in 1972, and tax advantages were given to any productive activity. This resulted in the establishment of industries, dedicated to consumer electronics-specific sectors, which demanded a significant number of new labor. The industries settled in the only two existing urban centers on the Isla Grande of TDF at that time, Ushuaia and Río Grande. Consequently, these cities grew rapidly and continuously as a result of significant internal migratory dynamics. However, economic impulse was not accompanied by urban planning regulations and housing accessibility policies. As a result of urban sprawl under scarce state management, and the lack of available housing, informal production of the city began to grow. Informality is a characteristic modality of Latin American ...